Zealous reformers and deadly laws : battling stereotypes - Kishwar, Madhu (Sage Publications, 2008)
Iris Marion Young was a world-renowned feminist moral and political philosopher whose many books and articles spanned more than three decades. She explored issues of social justice and oppression theory, the phenomenology of women's bodies, deliberative democracy and questions of terrorism, violence, international law and the role of the national security state. Her works have been of great interest to those both in the analytic and Continental philosophical tradition, and her roots range from critical theory (Habermas and Marcuse), and phenomenology (Beauvoir and Merleau Ponty) to poststructural psychoanalytic feminism (Kristeva and Ingaray). This anthology of writings aims to carry on the fruitful lines of thought she created and contains works by both well-known and younger authors who explore and engage critically with aspects of her work. The essays include personal remembrances as well as a last interview with Young about her work. The essays are organized into topic areas that are of interest to students in advanced undergraduate and graduate courses in ethics, feminist theory, and political philosophy.